The Influence of Work Incentives and Discipline on Employee Performance at PT. Penta Artha Impression - Santoso, Arief Budi; Sendouw, Magdalena Cristine (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
This research aims to determine the effect of incentives and work discipline on employee performance at PT Penta Artha Impression using quantitative methods. The study involved 85 respondents selected through a saturated sampling technique. Data analysis included linear regression, correlation coefficient, determination coefficient, and hypothesis testing. Results showed that incentives significantly affect employee performance, as indicated by the simple linear regression equation Y = 13.352 + 0.452X1, a correlation value of 0.655, and a determination value of 0.429, meaning incentives contribute 42.9% to employee performance. Hypothesis testing revealed tcount > ttable (7.896 > 1.989), thus rejecting H01 and accepting Ha1, confirming a significant impact of incentives on performance. Similarly, work discipline significantly affects employee performance, evidenced by the regression equation Y = 14.973 + 0.358X2, a correlation value of 0.639, and a determination value of 0.408, indicating a 40.8% contribution to performance. Hypothesis testing showed tcount > ttable (7.569 > 1.989), rejecting H02 and accepting Ha2, indicating a significant influence of work discipline on performance. Furthermore, the combined effect of incentives and work discipline on performance is significant, as per the multiple linear regression equation Y = 10.009 + 0.283X1 + 0.203X2, with a correlation value of 0.707 and a determination value of 0.500, indicating a 50.0% influence. Hypothesis testing showed Fcount > Ftable (41.003 > 2.720), rejecting H03 and accepting Ha3, confirming a significant simultaneous influence of incentives and work discipline on employee performance at PT Penta Artha Impression.